Bromination of L-tryptophan in a Fermentative Process With Corynebacterium glutamicum - Veldmann, Kareen H.; Dachwitz, Steffen; Risse, Joe Max; Lee, Jin-Ho; Sewald, Norbert; Wendisch, Volker F. (Frontiers in Bioengineering and Biotechnology, 2019)
Brominated compounds such as 7-bromo-L-tryptophan occur in nature. Many synthetic and natural brominated compounds have applications in the agriculture, food and pharmaceutical industries, for example, the 20S-proteasome inhibitor TMC-95A that may be derived from 7-bromo-L-tryptophan. Mild halogenation by cross-linked enzyme aggregates containing FAD-dependent halogenase, NADH-dependent flavin reductase and alcohol dehydrogenase as well as by fermentation with recombinant Corynebacterium glutamicum expressing the genes for the FAD-dependent halogenase RebH and the NADH-dependent flavin reductase RebF from Lechevalieria aerocolonigenes have recently been developed as green alternatives to more hazardous chemical routes. In this study, the fermentative production of 7-bromo-L-tryptophan was established. The fermentative process employed an L-tryptophan producing C. glutamicum strain expressing rebH and rebF from L. aerocolonigenes for halogenation and was based on glucose, ammonium and sodium bromide. C. glutamicum tolerated high sodium bromide concentrations, but its growth rate was reduced to half-maximal at 0.09 g L-1 7-bromo- L-tryptophan. This may be, at least in part, due to inhibition of anthranilate phosphoribosyltransferase by 7-bromo-L-tryptophan since anthranilate phosphoribosyltransferase activity in crude extracts was half-maximal at about 0.03 g L-1 7-bromo-L-tryptophan. Fermentative production of 7-bromo-L-tryptophan by recombinant C. glutamicum was scaled up to a working volume of 2 L and operated in batch and fed-batch mode. The titers were increased from batch fermentation in CGXII minimal medium with 0.3 g L-1 7-bromo-L-tryptophan to fed-batch fermentation in HSG complex medium, where up to 1.2 g L-1 7-bromo-L-tryptophan were obtained. The product isolated from the culture broth was characterized by NMR and LC-MS and shown to be 7-bromo-L-tryptophan.